Radial fillet flap following double ray amputation of the 2nd and 3rd fingers for invasive squamous cell carcinoma: a case report and review of the literature - Weller, Justin (International Surgery Journal, 2021)
Double ray amputation of the hand due to malignancy is extremely rare, with a paucity of published cases. We reviewed the literature and analysed our own experience in order to familiarise clinicians with this rare condition through a discussion of its diagnosis, management and prognosis. We present the case of a 54-year-old male with invasive squamous cell carcinoma (SCC) of the 2nd web space. He underwent a double ray amputation of the 2nd and 3rd fingers with a radial fillet flap and has begun range of motion exercises after six weeks. SCC of the hand requiring a double ray amputation is extremely rare. An MRI is required to accurately diagnose and manage this condition. The ray amputation technique is important for ensuring negative margins. A fillet flap should be used to close the defect as it provides a sensate web-space and improves motor function prognosis.